Absence of αβ T cells accelerates disuse bone loss in male mice after spinal cord injury. Issue 1 (26th October 2020) - Sahbani, Karim; Shultz, Laura C.; Cardozo, Christopher P.; Bauman, William A.; Tawfeek, Hesham A.
Abstract: Whether T cells promote bone loss following immobilization after spinal cord injury (SCI) remains undetermined. Therefore, wild‐type (WT) and T cell–deficient ( Tcrb −/− ) male mice underwent sham or contusion SCI to cause hindlimb paralysis. Femurs were isolated and distal and midshaft regions were evaluated by microcomputed tomography scanning. Bone marrow (BM) levels of bone turnover markers, as well as receptor activator of nuclear factor‐kappa B ligand (RANKL) and osteoprotegerin (OPG), were measured by ELISA. At 2 weeks post‐SCI, immobilization resulted in marked reduction in trabecular fractional bone volume (55%), thickness (40%), connectivity, and cortical thickness only in the Tcrb −/− animals (interaction with P < 0.05). BM analysis revealed lower bone formation (procollagen type 1 intact N‐terminal propeptide), higher bone resorption (tartrate‐resistant acid phosphatase‐5b), and a higher RANKL/OPG ratio in the Tcrb −/− SCI animals. At 5 weeks post‐SCI, while both WT and Tcrb −/− paralyzed animals showed deterioration of all indices of bone structure, they were more severe in Tcrb −/− animals. In summary, unlike other skeletal disorders, loss of αβ T cells compromises, rather than preserves, skeletal integrity under conditions of immobilization. Abstract : We evaluated the effects of disruption of T cell function on the development of bone loss following motor‐complete paralysis due to SCI. Wild‐type immunocompetent and genetically modified T cell−deficient mice were spinal cord injured to cause complete hindlimb paralysis, and the effects on bone microarchitecture and markers of bone formation and resorption were evaluated.